Synthesis and antimicrobial activity of some of new 1,1,3-trisubstituted cyclobutane containing thiazoles, succinimide and phthalimide derivatives - Ahmedzade, M; Cukurovali, A; Koparir, M (Chem Soc Pakistan, 2003)
The synthesis of 1-phenyl-1-methyl-3-(2-chloro-1-oxoethyl) cyclobutane and 1-mesityl-1-methyl-3-(2-chloro-1-oxoethyl) cyclobutane derivative compounds were performed and the biological activities of some of these compounds were investigated against sixteen different fungi and yeasts and some of them found to be active against much of the bacteria and yeasts studied in the high concentrations.